Analisis Pengaruh Pertumbuhan Ekonomi, Upah Minimum, dan Pengangguran terhadap Kemiskinan di Kota Semarang Tahun 2002-2021 - Kevin Hotmatius Pakpahan; Nugroho Sumarjiyanto Benedictus Maria (Universitas Diponegoro, 2022)
This study aims to analyze the effects of economic growth, minimum wage, and unemployment on poverty in Semarang City from 2002 to 2021. This research employs the Ordinary Least Squares (OLS) method. The results show that economic growth does not significantly affect the poverty rate in Semarang City during this period. The minimum wage variable has a negative and significant effect on the poverty rate in Semarang, while unemployment does not significantly affect the poverty rate. The variables of economic growth, minimum wage, and unemployment in Semarang City from 2002 to 2021 have a simultaneous effect on the poverty rate in Semarang during the same period.